2021
DOI: 10.1136/bmjopen-2021-055142
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of simplified HCV care on linkage to care amongst high-risk patients at primary healthcare clinics in Malaysia: a prospective observational study

Abstract: IntroductionTo achieve the elimination of hepatitis C virus (HCV), substantial scale-up in access to testing and treatment is needed. This will require innovation and simplification of the care pathway, through decentralisation of testing and treatment to primary care settings and task-shifting to non-specialists. The objective of this study was to evaluate the feasibility and effectiveness of decentralisation of HCV testing and treatment using rapid diagnostic tests (RDTs) in primary healthcare clinics (PHCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The modified same-day test-and-treat model was adapted from the existing practice in Malaysia (see Fig. 1 ) [ 19 ]. The implementation of this model in the current study was led by the Ministry of Health and did not receive any external funding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modified same-day test-and-treat model was adapted from the existing practice in Malaysia (see Fig. 1 ) [ 19 ]. The implementation of this model in the current study was led by the Ministry of Health and did not receive any external funding.…”
Section: Methodsmentioning
confidence: 99%
“…Only individuals who met the following criteria were eligible for the current study: (i) were at least 18 years of age, (ii) had a history of intravenous drug use, (iii) tested positive for anti-HCV, and (iv) were naïve to DAA-based treatment. The required sample size for the study was 194, as estimated based on a pilot project of HCV care decentralization in Malaysia, which reported that 83.8% of anti-HCV-positive participants were HCV RNA positive [ 19 ]. The formula used for the sample size calculation was the single proportion estimation formula [ 25 ], with a fixed level of confidence of 90% and a precision of 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HEAD-Start study was a collaborative project between the Foundation for Innovative New Diagnostics (FIND), the Drugs for Neglected Diseases initiative (DND i ) and the Ministry of Health (MOH), aiming to decentralize hepatitis C screening and treatment through 25 PHC clinics across Malaysia. It targeted adults aged between 18 and 70 years who sought primary care or harm reduction services and were found to have a positive serological rapid diagnostic test (RDT) result for HCV between December 2018 and December 2019 9 . Participants with a positive RDT result were then referred to one of the five selected tertiary hospitals for confirmatory diagnosis of hepatitis C (based on HCV ribonucleic acid (RNA) test using the reverse transcription polymerase chain reaction technique), laboratory biochemical tests and liver stiffness assessment using transient elastography (TE).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is often challenging to diagnose cirrhosis among potential treatment recipients in PHC settings due to the lack of facilities for imaging and biopsy 3 , 8 . Referring them to hospitals just for cirrhosis status assessment often results in loss to follow-up attributable to the stigma, logistical barriers and unaffordable transportation costs 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%